?????? ??????? ???? ????? ????? ???????? ????????? ?????? ????? ??????? ?????? ???? ???? ???? ???????? ????????? ???????? - Rahmat Dandan Pranawa; Umi Hanifah (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2020)
The majority of Eighth grade students at Sunan Kali Jaga Islamic High School Surabaya are weak in our Islamic scholarship. They have difficulty in composing sentences in accordance with the correct rules of writing Arabic. This study aims to determine how effective the use of the game